Penerapan Model Pembelajaran Numbered Head Together dalam Bimbingan Kelompok untuk Meningkatkan Motivasi Belajar Siswa Kelas VI SD Inpres Minasaupa 1 Kota Makassar - Wahid, Abdul; Afni, Nur (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to describe the learning motivation of sixth grade students at SD Inpres Minasaupa I Makassar after being taught by using Numbered Head Together method.2. This study aims to determine the effect of applying the Numbered Head Together method in group guidance to increase the learning motivation of sixth grade students at SD Inpres Minasaupa I Makassar. Research subjects of sixth grade students (15 students of control group and 15 students of experimental group) at SD Inpres Minasaupa I Makassar in academic year 2020/2021. The results showed that: 1) The level of learning motivation of sixth grade students at SD Inpres Minasaupa I Makassar after being taught by using Numbered Head Together method in group guidance in the experimental group showed that the level of student learning motivation increased, This means that there is a difference in the level of learning motivation between students who are taught by using of the Numbered Head Together method in group guidance and students who are not taught by using the Numbered Head Together method in group guidance, 2) Giving the Numbered Head Together method in group guidance can increase students' learning motivation.Â